(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The design of a mechatronic module intended for early fire detection and automatic suppression is of significant importance. The structural scheme described in the article includes processes for rapid fire hazard detection, signal processing, and activation of the fire suppression mechanism. This article discusses the description, structure, and operating principles of the fire detection and suppression device.